Genome-wide analysis of circular RNAs in prenatal and postnatal pituitary glands of sheep. Issue 1 (December 2017) - Li, Cunyuan; Li, Xiaoyue; Ma, Qiman; Zhang, Xiangyu; Cao, Yang; Yao, Yang; You, Shuang; Wang, Dawei; Quan, Renzhe; Hou, Xiaoxu; Liu, Zhijin; Zhan, Qianqian; et al.
Abstract Circular RNAs (circRNAs) are a class of animal non-coding RNAs and play an impor-tant role in animal growth and development. However, the expression and function of circRNAs in the pituitary gland of sheep are unclear. Transcriptome profiling of circRNAs in the pituitary gland of sheep may enable us to understand their biological functions. In the present study, we identified 10, 226 circRNAs from RNA-seq data in the pituitary gland of prenatal and postnatal sheep. Reverse transcription PCR and DNA sequencing analysis confirmed the presence of several circRNAs. Real-time RT-PCR analysis showed that sheep circRNAs are resistant to RNase R digestion and are expressed in prenatal and postnatal pituitary glands. GO and KEGG enrichment analysis showed that host genes of differentially expressed circRNAs are involved in the regulation of hormone secretion as well as in several pathways related to these processes. We determined that numerous circRNAs interact with pituitary-specific miRNAs that are involved in the biologic functions of the pituitary gland. Moreover, several circRNAs contain at least one IRES element and open reading frame, indicating their potential to encode proteins. Our study provides comprehensive expression profiles of circRNAs in the pituitary gland, thereby offering a valuable resource for circRNA biology in sheep.